Distance Learning Innovation in Teaching Chemistry in Vocational School Using the Concept of Isotherm Adsorption of Carbon Microparticles - Dani Nandiyanto, Asep Bayu; Siti Nur Hofifah; Santiuly Girsang, Gabriela Chelvina; Trianadewi, Dina; Ainisyifa, Zia Nazaliah; Siswanto, Adam; Putri, Silmi Ridwan; Anggraeni, Sri; Maryanti, Rina; Muslimin, Zannurain (Journal of Technical Education and Training, 2022)
The purpose of this study was to demonstrate distance learning innovation in teaching chemistry in vocational school using the concept of isotherm adsorption of carbon microparticles. The subjects were 60 vocational school students in Bandung, Indonesia, who took a 15-question pre-test and post-test with a learning video for supporting distance learning process. The subjects were focused to understand the successful teaching process, which were divided into the control class and the experimental class. The control class was done by giving a video containing conventional teaching process (without experimental demonstration), while the experimental class was done by giving a video containing experimental demonstration. To support the teaching process, the experimental video was chosen as the suitable teaching medium, including the production of carbon microparticles, adsorption measurement, data analysis, and an explanation of the adsorption mechanism. The results showed increases in the post-test scores compared to the pre-test. The t critical two-tailed value was 2.04, which was higher than the t statistic value (-2.52), ensuring the successful teaching for improving the students’ understanding on carbon adsorption phenomena. The learning video was provided visual and audio experiences. Video learning media gave positive impacts to students’ understanding, which was prospective for distance learning process. However, additional experimental demonstration inside the video learning media enhanced student’s interest in particular subjects and motivated them to learn more about the teaching subject, in which this become new innovation in the distance learning process. This study demonstrated the importance of combination between experimental demonstration and video as a teaching media for improving students’ comprehension, which can be implemented during special condition, for example COVID-19 pandemic.